Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1882)
Demorest's Family Magazine. December 1882. Vol. 19, No. 2. -- Bachelor Brindle's Christmas -- Modern Luxury in Living -- The Story of Klopstock -- One and the Other -- A Christmas Dream -- Our Pets -- Three Christmas Eves -- You're no Children -- Christmas Folk Lore and the Tree -- Hans and Gretel House -- Home Art and Home Comfort -- Talks with Women -- The Admiral's Ward -- Christmas in Art -- Current Topics -- Fancy Work -- What Women are Doing -- Kitchen -- Diamonds of Thought -- Spice box -- Mirror of Fashions -- Ladies' Club
Mme Demorest's Mirror of Fashions
New York Illustrated News
Digitized from original print, Valdosta State University Archives and Special Collections, June 16, 2017.
Keywords: Demorest's Family Magazine; Magazine; Illustrated Periodicals; Periodicals; Travel; Dressmaking; Homemaking; Needlework; Women; Catalogue; Children; Social History; Women's History; Fashion; United States; 1800s; 19th Century